(Re)discovering the lost middle: intergenerational inheritances and economic inequality in urban and regional research. Issue 10 (3rd October 2018) - MacLeavy, Julie; Manley, David
ABSTRACT: This paper calls for deepening understandings of inequality and the reproduction of inequality across the income distribution. In particular, it brings intergenerational transmissions and place effects, their interaction and progression over time into greater focus. The objective is to understand the implications of increasing inequality for those in the large and under-researched 'middle group'. The paper makes the case for urban and regional research that uses extensive longitudinal data, both qualitative and quantitative, to reveal the totality of the processes impacting the middle group, from those who are just managing to those who are advancing and flourishing.